A systems approach to the policy-level risk assessment of exotic animal diseases: network model and application to classical swine fever. - Delgado, Joao Pedro Correa; Pollard, Simon J. T.; Snary, E. L.; Black, Edgar; Prpich, George; Longhurst, Philip J. (Blackwell Publishing Ltd, 2013)
Exotic animal diseases (EADs) are characterized by their capacity to spread global distances, causing impacts on animal health and welfare with significant economic consequences. We offer a critique of current import risk analysis approaches employed in the EAD field, focusing on their capacity to assess complex systems at a policy level. To address the shortcomings identified, we propose a novel method providing a systematic analysis of the likelihood of a disease incursion, developed by reference to the multibarrier system employed for the United Kingdom. We apply the network model to a policy-level risk assessment of classical swine fever (CSF), a notifiable animal disease caused by the CSF virus. In doing so, we document and discuss a sequence of analyses that describe system vulnerabilities and reveal the critical control points (CCPs) for intervention, reducing the likelihood of U.K. pig herds being exposed to the CSF virus.
Keywords: Analysis, classical swine fever, exotic animal disease, import, network, risk, system